Analysing ICT and Development from the Perspective of the Capabilities Approach: A Study in South Brazil - and Coelho, Taiane Ritta; Segatto, Andréa Paula; Frega, José Roberto (The Electronic Journal of Information Systems in Developing Countries, 2015)
Certain international agencies propose that Information and Communication Technology (ICT) allows development to be reached more efficiently and quickly. While there are success stories galore, there is acknowledgement of not all investments in ICT bringing positive effects towards development. Following the Capabilities Approach, this paper discusses how the use of ICT can promote a more effective development by studying the case of Sudotec (association for technological and industrial development), a non-profit organization that saw in ICT the opportunity to change the local scenario. The results revealed positive effects of the use of ICT in social, economical and cultural spheres, but not presenting political effect.